Phylogenetic relationships and evolutionary history of the greater horseshoe bat, Rhinolophus ferrumequinum, in Northeast Asia - Liu, Tong; Sun, Keping; Park, Yung Chul; Feng, Jiang (PeerJ, 2016)
The greater horseshoe bat, Rhinolophus ferrumequinum, is an important model organism for studies on chiropteran phylogeographic patterns. Previous studies revealed the population history of R. ferrumequinum from Europe and most Asian regions, yet there continue to be arguments about their evolutionary process in Northeast Asia. In this study, we obtained mitochondrial DNA cyt b and D-loop data of R. ferrumequinum from Northeast China, South Korea and Japan to clarify their phylogenetic relationships and evolutionary process. Our results indicate a highly supported monophyletic group of Northeast Asian greater horseshoe bats, in which Japanese populations formed a single clade and clustered into the mixed branches of Northeast Chinese and South Korean populations. We infer that R. ferrumequinum in Northeast Asia originated in Northeast China and South Korea during a cold glacial period, while some ancestors likely arrived in Japan by flying or land bridge and subsequently adapted to the local environment. Consequently, during the warm Eemian interglaciation, the Korea Strait, between Japan and South Korea, became a geographical barrier to Japanese and inland populations, while the Changbai Mountains, between China and North Korea, did not play a significant role as a barrier between Northeast China and South Korea populations.
Keywords: Rhinolophus; Phylogeography; Mitochondrial DNA; Northeast Asia